2011
DOI: 10.1590/s0102-05362011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic traits and chemical composition of single hybrids of sweet corn

Abstract: In Brazil, the greengrocery market of sweet corn has been expanding along the country. In contrast, there have been few agriindustries canning sweet corn (Zea mays) because of the lack of cultivars with agronomic characteristics proper to industrial purposes. The purpose of this study was to evaluate the general combining ability (GCA) of seven inbred lines of sweet corn, and the specific combining ability (SCA) of their hybrid combinations based on their agronomic traits, and the chemical composition of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Among these inbred lines, favorable estimates of GCA were observed in L 3 for TSS; L 1 , L 6 , L 9 , L 7' and L 9' for flowering and height of plants; L 1 , L 6 , L 7' and L 9' for ear height; L 9 , L 1' and L 9 for ear length; L 1 , L 3 , L 6 , L 1' and L 7' for number of grain rows (Table 3). These favorable estimates of GCA highlighted higher accumulation of favorable alleles for these traits (Cruz et al, 2004;Kwiatkowski et al, 2011). In their study on diallels of super sweet corn inbred lines, Elayaraja et al (2014) and Suzukawa et al (2018) highlighted that it is difficult to obtain inbred lines with good general combining ability for productivity and total soluble solids, this trend being observed in this study, with an only exception of L 3 inbred line.…”
Section: General Combining Ability Of Inbred Lines Of Group II (ĝ J )supporting
confidence: 49%
See 3 more Smart Citations
“…Among these inbred lines, favorable estimates of GCA were observed in L 3 for TSS; L 1 , L 6 , L 9 , L 7' and L 9' for flowering and height of plants; L 1 , L 6 , L 7' and L 9' for ear height; L 9 , L 1' and L 9 for ear length; L 1 , L 3 , L 6 , L 1' and L 7' for number of grain rows (Table 3). These favorable estimates of GCA highlighted higher accumulation of favorable alleles for these traits (Cruz et al, 2004;Kwiatkowski et al, 2011). In their study on diallels of super sweet corn inbred lines, Elayaraja et al (2014) and Suzukawa et al (2018) highlighted that it is difficult to obtain inbred lines with good general combining ability for productivity and total soluble solids, this trend being observed in this study, with an only exception of L 3 inbred line.…”
Section: General Combining Ability Of Inbred Lines Of Group II (ĝ J )supporting
confidence: 49%
“…The trials showed adequate experimental accuracy for most evaluated traits, when compared to other experiments with super sweet corn (Kwiatkowski et al, 2011;Santos et al, 2014) (Table 1). The average squares for treatments, hybrids and their unfolding in GCA-I, GCA-II and SCA, for the traits evaluated in two sowing dates, were significant, with exception of "days to flowering" in the second sowing date (Table 1).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Over the last several years, sweet corn production improvements in Brazil have consisted of obtaining hybrids (Kwiatkowski et al, 2011) and assessing diverse germplasm (Almeida et al, 2011;Terra et al, 2011) to form a broad genetic basis for local farmers. Information about genetic diversity in corn is essential to germplasm characterization and utilization (Gerdes and Tracy, 1994;Kashiani et al, 2012;Liu et al, 2003;Nigussie and Saleh, 2007;Revilla et al, 2005;Srdić et al, 2011;Tracy et al, 2000;Yousef and Juvik, 2001), particularly among the sul germplasm from southern Brazil (Amorin et al, 2003;Barbosa-Neto et al, 2005;Bered et al, 2005;Rupp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%